Seizing history: development and non-climate change in Small Island Developing States - Godfrey Baldacchino (International Journal of Climate Change Strategies and Management, 2018)
Purpose – This paper offers a critical review of climate change related initiatives in small island states, including Small Island Developing States (SIDS), which can end up as ontological traps: fuelled and supported by external donor agencies, thwarting out-migration and shifting scarce and finite resources away from other, shorter-term and locally spawned development trajectories and objectives. Design/methodology/approach – This paper is based on a selective literature review. It clusters important themes found in published research and policy documents. Findings – The results identify a burgeoning critical voice in regards to resilience and its legitimation of climate change driven projects in SIDS. This paper recommends a more nuanced approach which also privileges migration. Originality/value – This paper provided a critical overview and synthesis of the immobility implicit in much climate change related work, through the critical lens of island studies and post-colonial studies.